Code Mixing Used by The Teachers in Teaching English at Dharma Private English Course - Luh Putu Sania Esa Putri; Dewa Ayu Kadek Claria; Mirsa Umiyati (PRAGMATICA : Journal of Linguistics and Literature, 2024)
This research is titled Code Mixing Used by The Teachers in Teaching English at Dharma Private English Course. The objective of this research is to: 1) analyze the types of code-mixing inTeaching English at Dharma Private English Course, 2) analyze the reason of code-mixing in Teaching English at Dharma Private English Course. Data were analyzed using content analysis method based on the theory proposed by Muysken (2000) to identify types and Juu's (2009) theory and interviews with teachers from Dharma Private English Course to explain the reasons for code mixing. The findings of this study indicate that there are three types of code mixing that appear in teacher utterances: insertion (subject, object, and time adverbial), alternation (clause), and congruent lexicalization (noun phrase, verb phrase, and phonological structure) based on Muysken's theory. In terms of reasons for code mixing, there are two reasons that occur during the teaching and learning process: Language Dominance and Psycholinguistic Motivation based on theory Juu's (2009). And there is one main reason why teachers at Dharma Private English Course use code mixing in teaching, which is Improved Knowledge of Vocabulary.